Study of specific IgE and IgG4 antibodies to mite antigen in asthmatic children during immunotherapy - Hiroyuki Matsuoka; Yutaka Atsuta; Hisashi Matsubara; Motoi Adachi; Yukari Matsushita; Toshihide Obe; Katsuhiko Ando; Yasuo Chinzei (Allergology International, 1998)
Using immunoblotting and densitometer techniques, we followed the levels of IgE and IgG4 antibodies to Dermatophagoides farinae antigen in the sera of 12 asthmatic children during immunotherapy, repeated injections of house dust extract, for 2 years. The symptoms of asthma were reduced or disappeared by the 6th month after starting immunotherapy in 12 children. Two years later, RAST scores to house dust and D. farinae in each child were still 4 or 5. The levels of IgE antibodies to Der fII in all cases did not change drastically. IgE antibodies to higher molecular weight antigens (Der fI, fIII, fIV etc.) developed in some cases, suggesting that repeated injections of crude extract tended to induce IgE antibodies to alternative molecules in patients. The IgG4 antibody to Der fII increased in 10 cases, while that to Der fI increased in three of 12 cases, indicating that production of IgG4 antibodies to mite antigens started and expanded with repeated injections of house dust extract. The amount of induced IgG4 antibodies to Der fI and Der fII was not enough to inhibit the immunoblot reaction of IgE antibodies to these molecules.